TOILET KHUSUS PEREMPUAN DAN WARUNG KOPI DI BANDA ACEH (Sebuah Kajian Terhadap Konsep Keadilan Gender dan Gender Planning) - Fadlia, Faradilla; Darwin, Rizkika Lhena; Ramadani, Ismar (INTERNATIONAL JOURNAL OF CHILD AND GENDER STUDIES, 2016)
Become part of the public space in Banda Aceh, the coffee shop should be friendly to male and female gender. Because after the tsunami, women were in a coffee shop as a form of public involvement in public place have previously dominated by men. Even so, almost no coffee shop in the city of Banda Aceh that separate male and female toilets. Not to mention the condition of the toilets which tend to be clean and comfortable to use. It is not only forgotten by the management but also by women themselves. When referring to the concept of the concept of gender equality and gender planning then this condition could occur due to a lack of understanding of gender equality from the manager of a coffee shop or on the women themselves. Although the observations made, women tend to feel uncomfortable because of this issue, but they do not know how to communicate with the manager. As a conclusion that the coffee shop is not reserved for women. Even if women have become part of the coffee shop, the conclusions that coffee shop is not friendly to the female gender.